Evidence-Based Leadership in Nursing: An Evolutionary Concept Analysis - Hu, Shuang; Liu, Siying; Li, Xianfeng; Chen, Wenjun; Li, Jialin; Jiale, Hu; Välimäki, Maritta Anneli; Li, Xianhong (WILEY, 2026)
Aim To conduct a concept analysis of evidence-based leadership in a nursing context.
Methods Rodgers' evolutionary method was employed to identify attributes, antecedents, consequences, definitions and surrogate and related terms.
Data Source We systematically searched three databases (PubMed, Cumulative Index to Nursing and Allied Health Literature and Scopus) for relevant publications. The databases were searched from their inception to 4 February 2024.
Results We included 12 papers published between 2005 and 2022. The attributes include leadership attributes (personality, developing common goals and visions and influencing others) and evidence-based attributes (valuing evidence-based practice, integrating evidence and adapting evidence). The antecedents include individual internal factors (commitment to growth and proficiency in implementation science) and individual external factors (growing need for evidence-based practice, training support and available resources), while the consequences are personal growth, organisational benefit and disciplinary development. Based on the concept analysis, evidence-based leadership can be defined as a process whereby individuals, based on their personality and values towards evidence-based practices, integrate the best evidence into practice, adapt the evidence integration process based on evaluations and influence others towards achieving a common goal and vision.
Conclusions This concept analysis enhances our understanding of evidence-based leadership, guiding nurses to integrate evidence into their leadership practices to achieve specific goals and visions within the healthcare context. Future studies could consider developing instruments to evaluate evidence-based leadership based on this refined concept, ultimately promoting nurses' leadership competencies in real-world settings.
Implication for Nursing PracticeThis concept analysis not only raises awareness of the responsibilities of nurses as healthcare professionals, including the provision of evidence-based practice, but also facilitates their effective execution of these responsibilities. Empowering nurses to actively incorporate evidence into their leadership practices can further enhance the quality of healthcare delivery.
Reporting Method Not applicable.
Patient or Public Contribution Not applicable.